Designing a fully automated and integrated inventory and replenishment system for hospitals. Issue 1 (31st December 2023) - Jebbor, Sara; Chiheb, Raddouane; El Afia, Abdellatif; Gallab, Maryam
Abstract : Surge demand shows that hospital logistics automation is unexploited given that the high pressure in work, the lack of resources, and some inventory and replenishment problems still occur. Hospitals do not fully leverage the implemented automatic systems and integrate them into large-scale logistic processes. Only some tasks/ services are automated keeping nurses in charge of the logistic labour, a large stock space, and inventory and replenishment problems. Hospitals do not adopt strategies that carefully aim for a high level of logistics automation and integration, using adequate management systems/ policies to make it cost-effective. This paper presents the design of a fully automated and integrated system for asset inventory and replenishment management in hospitals. The strategy adopted in this work starts with choosing a proactive replenishment policy operating in real-time and a suitable inventory and replenishment system (RFID-enabled two-bin system). This system is then automated using adequate and recent technologies (e.g. 'Box-Picker', smart gravity-flow racks, and conveyors). The proposed system is modelled and simulated in a virtual hospital under a mass casualty incident. Results show a considerable reduction of assets unavailability (99.98% in the central pharmacy and 90.47% in wards) and stock space. Besides, nurses are released from logistic tasks.